Disclosure Practices of Intellectual Capital in Sri Lankan Context - Larojan, C.; Fernando, A.J. (Vavuniya Campus of the University of Jaffna., 2018)
In the today's Knowledge-Based Economy (KBE), Intellectual Capital (IC) is considered as a strategic asset which determines the value of the company. Different practices of disclosing the IC information in annual reports do not result in the real value of the financial position of the company, is the main problem in Sri Lankan companies. The objectives of this study are to examine the nature of disclosing the IC information based on the content analysis of annual reports and to reveal the significant findings of past Sri Lankan Intellectual Capital Disclosure (ICD) research studies. Most of the Sri Lankan listed companies are now being disclosed ICD in the text, sentences, pictures, tables and graphs with the core discipline of Global Reporting Initiative [GRI] guidelines in their annual reports. The study offers an insight into the corporate and business level managers, policy makers and potential investors.
Keywords: Global reporting initiative [GRI] guidelines; Intellectual capital (IC); Intellectual capital disclosure (ICD); Knowledge-based Economy (KBE)